2021
DOI: 10.1007/s12369-021-00805-6
|View full text |Cite
|
Sign up to set email alerts
|

Determining Shape and Size of Personal Space of a Human when Passed by a Robot

Abstract: Autonomous mobile robots that operate in environments with people are expected to be able to deal with human proxemics and social distances. Previous research investigated how robots can approach persons or how to implement human-aware navigation algorithms. However, experimental research on how robots can avoid a person in a comfortable way is largely missing. The aim of the current work is to experimentally determine the shape and size of personal space of a human passed by a robot. In two studies, both a hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Our main finding is that perceived comfort increases with passing distance following an inverted Gaussian. In our other work, the same relationship is found ( Neggers et al, 2022 ), and as we show in that paper, the same relationship can be found in the work of Pacchierotti et al (2006) . This gives further proof that an inverted Gaussian is an appropriate way of describing the relationship between passing distance and perceived comfort.…”
Section: Experiments 1: Passing Distancessupporting
confidence: 84%
See 4 more Smart Citations
“…Our main finding is that perceived comfort increases with passing distance following an inverted Gaussian. In our other work, the same relationship is found ( Neggers et al, 2022 ), and as we show in that paper, the same relationship can be found in the work of Pacchierotti et al (2006) . This gives further proof that an inverted Gaussian is an appropriate way of describing the relationship between passing distance and perceived comfort.…”
Section: Experiments 1: Passing Distancessupporting
confidence: 84%
“…It is still not clear whether the same rules of human social navigation apply to robots. In our earlier study ( Neggers et al, 2022 ), we found that a passing distance of 80 cm was indeed considered comfortable, but in this study, people were not moving but stationary.…”
Section: General Introductionmentioning
confidence: 51%
See 3 more Smart Citations